2009
DOI: 10.1007/s00253-009-1955-2
|View full text |Cite
|
Sign up to set email alerts
|

Production of pigment-free pullulan by swollen cell in Aureobasidium pullulans NG which cell differentiation was affected by pH and nutrition

Abstract: A black yeast strain "NG" was isolated from strawberry fruit and identified as Aureobasidium pullulans. Strain NG displayed yeast-like cell (YL), swollen cell (SC), septate swollen cell (SSC), meristematic structure (MS), and chlamydospore (CH) morphologies. pH was the key factor regulating cell morphogenesis of strain NG. Differentiation of YL controlled by extracellular pH had no relationship with nutrition level. YL was maintained at pH >6.0, but was transformed into SC at pH approximately 4.5. SC, a stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…When pH was 6.0, the cells remained mainly of yeast‐like form after 12 h cultivation and melanin began to accumulate in the cell after 48 h (data not shown here). Early work already confirmed that pH was the key factor regulating cell morphogenesis of strain A. pullulans . Li et al proved that yeast‐like cells (YL) controlled by extracellular pH had no relationship with nutrition level, which was maintained at pH > 6.0, but was transformed into a swollen cell (SC) at pH ∼4.5.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…When pH was 6.0, the cells remained mainly of yeast‐like form after 12 h cultivation and melanin began to accumulate in the cell after 48 h (data not shown here). Early work already confirmed that pH was the key factor regulating cell morphogenesis of strain A. pullulans . Li et al proved that yeast‐like cells (YL) controlled by extracellular pH had no relationship with nutrition level, which was maintained at pH > 6.0, but was transformed into a swollen cell (SC) at pH ∼4.5.…”
Section: Resultsmentioning
confidence: 95%
“…Early work already confirmed that pH was the key factor regulating cell morphogenesis of strain A. pullulans . Li et al proved that yeast‐like cells (YL) controlled by extracellular pH had no relationship with nutrition level, which was maintained at pH > 6.0, but was transformed into a swollen cell (SC) at pH ∼4.5. SC, a stable cell type of A. pullulans , could bud, separate, or transform into meristematic structure (MS) or chlamydospore (CH), in response to nutrition level and low pH.…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, a relatively high concentration of CaCO 3 (∼30 g/L) was used in this study to maintain the fermentation pH around 6 as well as to stimulate PMA production. A near‐neutral pH of 6–6.5 is important for the PMA biosynthesis because a lower pH may cause the hydrolysis of PMA (at pH < 5) (Holler et al, 1992) and induce the production of extracellular polysaccharides (at pH 4.5) and chlamydospore (at pH 3) (Li et al, 2009), which may compete for limited carbon source and result in lower PMA yield.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, a low pH may also induce the formation of by-product (e.g., extracellular polysaccharides) and chlamydospore by some strains of Aureobasidium spp. [ 42 ], which is undesirable in PMA production. Another reason for this is the significant role of CaCO 3 in the biosynthesis of malic acid.…”
Section: Discussionmentioning
confidence: 99%